ОСОБЛИВОСТІ КЕРУВАННЯ ЕЛЕКТРОННИМИ КЛЮЧАМИ В КВАЗІРЕЗОНАНСНИХ ІМПУЛЬСНИХ ПЕРЕТВОРЮВАЧАХ - Городній, О.М. (Інститут електродинаміки Національної академії наук України, 2018)
The features of the control of zero-current-switch quasi-resonant pulse converter (QRPC-ZCS) and zero-voltage-switch quasi-resonant pulse converter (QRPC-ZVS) are researched. The ways of the dynamic losses reduction when switching electronic switches are described. Also reasons for changing the parameters of currents and voltages in the resonant circuits of these converters, that changes their own frequency, and the consequences of this fact are substantiated. The principles of automatic quasi-control of electronic switches of these converters are considered, what simplifies the synthesis of control systems and reduces the dynamic losses in electronic switches. References 10, figures 4, table.